2023
DOI: 10.3389/fnut.2023.1162442
|View full text |Cite
|
Sign up to set email alerts
|

Causal associations between insulin-like growth factor 1 and vitamin D levels: a two-sample bidirectional Mendelian randomization study

Zhaoyang Gou,
Fan Li,
Fengzhen Qiao
et al.

Abstract: BackgroundInsulin-like growth factor 1 (IGF-1) plays a vital role in the attainment and maintenance of bone mass throughout life and is closely related to the stature of children. 25-Hydroxyvitamin D (25-OHD) is an intermediate of vitamin D (Vit D) metabolism and a key indicator of Vit D nutritional status. Multiple studies have revealed that IGF-1 levels undergo a non-significant increase after Vit D supplementation. Here, we analyzed the causal and reverse causal relationships between 25-OHD and IGF-1 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Vitamin D is a fat-soluble micronutrient with pleotropic effects on human health. 6 Observational studies have reported that vitamin D deficiency, as evidenced by low circulating concentrations of its major metabolite 25-hydroxyvitamin D (25(OH)D), associates with slower linear growth, 7 reduced lean mass, 8 childhood obesity [9][10][11] and precocious puberty, 12 13 potentially reflecting the ability of vitamin D to stimulate production of insulinlike growth factor 1 14 and regulate adipogenesis. 15 A phase 2 randomised controlled trial (RCT) conducted in Mongolia reported that a 6-month course of vitamin D supplementation increased height gain in 113 vitamin D deficient schoolchildren aged 12-15 years, 16 but these results were not confirmed by a recent phase 3 RCT conducted in the same setting.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Vitamin D is a fat-soluble micronutrient with pleotropic effects on human health. 6 Observational studies have reported that vitamin D deficiency, as evidenced by low circulating concentrations of its major metabolite 25-hydroxyvitamin D (25(OH)D), associates with slower linear growth, 7 reduced lean mass, 8 childhood obesity [9][10][11] and precocious puberty, 12 13 potentially reflecting the ability of vitamin D to stimulate production of insulinlike growth factor 1 14 and regulate adipogenesis. 15 A phase 2 randomised controlled trial (RCT) conducted in Mongolia reported that a 6-month course of vitamin D supplementation increased height gain in 113 vitamin D deficient schoolchildren aged 12-15 years, 16 but these results were not confirmed by a recent phase 3 RCT conducted in the same setting.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The obese group had higher levels of IGF-1 and IGFBP3 than the eutrophic group and both had higher levels than the undernourished patients. During childhood growth and development, growth hormone (GH) induces hepatic synthesis of IGF-1, increasing the activity of P450 in hepatic mitochondria, which directly induces the 25-hydroxylation of Vit-D, increasing its serum concentration [85]. In a double-blind, placebo-controlled study with 117 children (4-8 years) at baseline, Vit-D was positively associated with muscle strength, FFMI, and IGFBP3.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Vitamin D is a fat-soluble micronutrient with pleotropic effects on human health. 6 Observational studies have reported that vitamin D deficiency, as evidenced by low circulating concentrations of its major metabolite 25-hydroxyvitamin D (25[OH]D), associates with slower linear growth, 7 reduced lean mass, 8 childhood obesity [9][10][11] and precocious puberty, 12,13 potentially reflecting the ability of vitamin D to stimulate production of insulin-like growth factor 1 14 and regulate adipogenesis. 15 A phase 2 randomised controlled trial (RCT) conducted in Mongolia reported that a 6-month course of vitamin D supplementation increased height gain in 113 vitamin D deficient schoolchildren aged 12-15 years, 16 but these results were not confirmed by a recent phase 3 RCT conducted in the same setting.…”
Section: Introductionmentioning
confidence: 99%